ANALISIS DAYA DUKUNG LINGKUNGAN PERAIRAN MARIKULTUR BATAM ESTET (BME) BATAM - Sachoemar, Suhendar I (Jurnal Hidrosfir Indonesia, 2006)
Carrying capacity analysis at Bantam Mariculture Estate was conducted todetermain their optimal production capacity and number of fish cages settingfor sustainable aquaculture development within this area. The analysis wasdesign on the material balance base of the nitrogen input and output wherethe aquaculture system of fish rearing on the cages was assumed as theblack box system. To support the analysis, physical and chemical parameters such as current speed and dissolved in organic nitrogen (ammonia, nitrate and nitrite) were included on the analysis to understand their flushing rate as key factor that showing of the ecosystem ability on the reduction of the pollutant concentration.The calculation result shows that fish production capacity of BatamMariculture Estate was high that is up to 3 thousand ton peryear for 3thousand unit of fish cages. Flushing rate was excellent that is within rangeof 30 – 60 million m3/hours with the ability of the ecosystem to avoid thepollutant is less than 10 hours. The nitrogen and ammonia released on theenvironment are low that are around 0.004 – 0.008 mg/days and 0.002 –0.004 mg/days respectively. These value are below of the minimum levelpermitted for the aquaculture.